The Potential and Challenges of Digital Well-Being Interventions: Positive Technology Research and Design in Light of the Bitter-Sweet Ambivalence of Change - Diefenbach, Sarah (Frontiers in Psychology, 2018)
Along with the dissemination of technical assistance in nearly every part of life, there has been growing interest in the potential of technology to support well-being and human flourishing. "Positive technology" thereby takes the responsible role of a "digital coach", supporting people in achieving personal goals and behavior change. The design of such technology requires knowledge of different disciplines such as psychology, design and human-computer interaction. However, possible synergies are not yet used to full effect, and it needs common frameworks to support a more deliberate design of the "therapeutic interaction" mediated through technology. For positive technology design, positive psychology and resource oriented approaches appear as particularly promising starting point. Besides a general fit of the basic theoretical conceptions of human change, many elements of established interventions could possibly be transferred to technology design. However, besides the power of focusing on the positive, another psychological aspect to consider are the bitter components inherent to change, such as the confrontation with a negative status quo, threat of self-esteem, and the effort required. The present research discusses the general potential and challenges within positive technology design from an interdisciplinary perspective with theoretical and practical contributions. Based on the bitter-sweet ambivalence of change as present in many psychological approaches of motivation and behavior change, the bitter-sweet continuum serves as a proxy for the mixed emotions and cognitions related to change. An empirical investigation of those factors among 177 users of self-improvement technologies provides initial support for the usefulness of the bitter-sweet perspective in understanding change dynamics. In a next step, the bitter-sweet concept is transformed into different design strategies to support positive change. The present article aims to deepen the discussion about the responsible role of technology as a well-being enhancement tool and to provide a fruitful frame for different disciplines involved in positive technology. Two aspects are highlighted: First, investigating well-being technology as a form of "therapeutic interaction", focusing on the need for sensible design solutions in the emerging dialogue between technology and user. Second, a stronger consideration of the bitter-sweet ambivalence of change, utilizing (positive) psychology interventions to full effect.